PERSEPSI MASYARAKAT TERHADAP PELAYANAN PUSKESMAS KECAMATAN BLANG BINTANG KABUPATEN ACEH BESAR - Raihani - (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2013)
One of the institutions that society is always associated with the clinic, each institution has always wanted to be the best by the community, as well as health centers Blang Bintang district of Aceh Besar district. The higher and better the service given employee, the higher the public interest in the health center services, and the better the welfare of the public health. So the point of balance that benefits both parties can be realized. The problem of this research is how the public's perception of health center services Blang Bintang district of Aceh Besar district. This study uses a quantitative approach. Type of research is a descriptive study. The research was conducted at Blang Bintang district of Aceh Besar district. Population in this research is all the people in the District of Blang Bintang ever treated three times at Blang Bintang Health Center is spread across 26 villages. While the sample is as many as 50 people. Sampling was done by cluster sampling (ie taking a few clusters of the population at random, then take it all or partly elements of each clump is chosen to be sampled). Data collection techniques such as library research and field research in the form of questionnaires and interviews. Data processing techniques used are descriptive statistics (percentages). Research results show that the public's perception of health center services Bintang district of Aceh Besar regency star overall was 4.28. With reference to the opinion Ruaida (in chapters in point 3.4) then this figure can be categorized into the very good category. Thus we can conclude that the public's perception of health center services Blang Bintang district of Aceh Besar district is very good.Â Key words: public perception, care, health center